2021
DOI: 10.1039/d1ra04054e
|View full text |Cite
|
Sign up to set email alerts
|

A model of modified meta-iodobenzylguanidine conjugated gold nanoparticles for neuroblastoma treatment

Abstract: 127I-modified mIBG was successfully synthesized and grafted covalently to the surface of carboxylated PEG-GNPs. The particles were not toxic to the normal fibroblast cells while specifically internalized into neuroblastoma cells line via NET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…81 Previous studies showed even when attached to nanoparticles, MIBG derivatives target the same uptake-1 mechanism through the NETs. 82,83 This can be presumed to apply to our system as well. The only exception that we have reported is in the instance of excess MIBG, which triggers a nonspecific enhanced uptake.…”
Section: In Vitro 2p-pdtmentioning
confidence: 99%
“…81 Previous studies showed even when attached to nanoparticles, MIBG derivatives target the same uptake-1 mechanism through the NETs. 82,83 This can be presumed to apply to our system as well. The only exception that we have reported is in the instance of excess MIBG, which triggers a nonspecific enhanced uptake.…”
Section: In Vitro 2p-pdtmentioning
confidence: 99%
“…In both diagnostics and therapeutics, nanoparticles represent an alternative to traditional radiation-based modalities . Whereas MIBG relies on radiation signatures to achieve spatial resolution, nanoparticles can be easily labeled with nonradio modalities (fluorescence, photoacoustic) for identification in the tissue. , Many nanoparticle platforms can be easily loaded with therapeutics, including single components or combinations thereof, of chemotherapeutics, photodynamic, or photothermal agents. For tumor tissues specifically, nanoparticles are even known to naturally (“passively”) accumulate, a process known as the enhanced permeability and retention (EPR) effect. , Despite having a nanocarrier size (>20 nm) far larger than the NET pore, MIBG-inspired compounds conjugated to nanoparticle surfaces have been reported to exhibit over a 4× increase in uptake compared with nonconjugated controls in neuroblastoma (NB) cell lines. , …”
mentioning
confidence: 99%